Inequality and democratic egalitarianism 'Marx's economy and beyond' and other essays - Harvey, Mark, 1943- (Manchester Political Studies, 2018)
This book analyses what generates the extreme inequalities in rights to income, property and public goods in contemporary societies across the world today.